Impact of Artificial Intelligence on Management Decision-Making - Ashritha, Pilly; Reddy, Patlolla Sathvika (International Journal of Advances in Business and Management Research (IJABMR), 2023)
Artificial intelligence (AI) has become a game-changer for management decision-making in this age of rapid technological innovation. This study explores how artificial intelligence (AI) is revolutionizing managerial procedures. It looks at the various ways that AI is affecting and changing the landscape of decision-making, as well as how AI-driven algorithms and data analytics are enhancing human decision-making to produce more informed and data-driven decisions. The paper concludes that AI has the potential to revolutionize management decision-making and also make better decisions that improve their outcomes by comparing different fields where AI is used.